Internal mode control based coordinated controller for brushless doubly fed induction generator in wind turbines during fault conditions - Ahsanullah Memon; Mohd Wazir Mustafa; Attaullah Khidrani; Farrukh Hafeez; Shadi Khan Baloach; Touqer Ahmed Jumani (Institute of Advanced Engineering and Science, 2021)
Brushless double fed induction generator (BDFIG) based machines have gained popularity in wind turbine applications because of their easily accessible design. Low voltage ride through (LVRT) is critical for the reliable integration of renewable energy with the power grid. The refore, LVRT capability of brushless DFIGs makes them an attractive choice for maintaining voltage stability in grid. The existing works on BDFIG control suffer from two major drawbacks. Firstly, the methodology does not consider LVRT as a design metric, and secondly, these techniques do not have any means for coordinating between a machine side inverter (MSI) and grid side inverter (GSI). This results in sub-optimal controller design and eventually result in the violation of grid code requirements. To solve these issues, this paper proposes the use of brushless DFIGs in wind turbines using a control technique based on analytical modeling. Moreover, employing internal model control (IMC), the proposed technique can effectively coordinate the control between the MSI and GSI resulting in reduced oscillations, overshoots and improved stability under fault conditions. Furthermore, the simulation results for wind turbine generators show that the proposed scheme significantly improves the stability and compliance of grid codes ascompared to the existing hardware techniques.